Performance evaluation of a terrain-accommodating oil palm loose fruit collector - Janius, Rimfiel B.; Eskandar, Abadanjumi (Universiti Putra Malaysia Press, 2007)
A chain-and-rake type oil palm loose fruit collector was designed and developed. With a nose width of 220 mm and two 360-mm diameter wheels the machine is able to accommodate the varying conditions of terrain, vegetation and residue around an oil palm tree. The machine was tested at an engine speed of 470 rpm resulting in a linear rake speed of 52.4 m/min. Pick-up ability on seven types of surfaces and manoeuvrability in ten different conditions was tested. Evaluation of collector pick-up ability reveals that machine characteristic length, nose width and height and correct finger-ground clearance are the most important machine parameters determining the ability of the collector to follow the terrain. For collector manoeuvrability, the affecting factors are the front wheel support and location of the rear wheels as a pivot. In all successful pick-up attempts, the machine picks up the fruits free of injury. While the characteristic length negotiates the terrain at the macro level, the nose does it at the micro level. The ability of the machine to operate in areas of vegetation and residues depends largely on the picking device, which has been able to comb through most vegetation and filter out smaller to medium size residues.